A new species of Smythea (Rhamnaceae) from New Guinea - Utteridge, Timothy M.a.; Cahen, Daniel (Phytotaxa, 2021)
A new species of the genus Smythea is described and illustrated from Papua New Guinea. This new taxon, Smythea papuana, is morphologically similar to S. oblongifolia, a species widespread in Malesia reaching the Lesser Sunda Islands and Maluku Islands. It is the first inland species of Smythea in New Guinea to be described – the only other species known to occur on the island is the widely distributed and coastal S. lanceata. An amendment to the key to the genus is provided.